High endemic freshwater mussel (Bivalvia: Unionida) diversity in western Borneo, with description of three new species - Alexandra, Zieritz; John, Pfeifer; Khairul Adha, A. Rahim; Hari, Prayogo; Muhammad Sofwan, Anwari; Farah, Diba; Elsa, Froufe; Tabitha, Blackwell; Hanna, Hartikainen; Manuel, Lopes-Lima (The Linnean Society of London, 2024)
Te freshwater mussels (Bivalvia: Unionida) of the biodiversity hotspot Sundaland are experiencing severe anthropogenic threats, whilst their diversity and distribution remain poorly understood. Here, we present the frst modern-day data on Unionida diversity and distribution across western Borneo. Mussels were surveyed and collected in the upper Kapuas and Pawan river basins in West Kalimantan, Indonesia, and the Sambas Besar, Sarawak and Batang Sadong river basins in Sarawak, Malaysia. DNA sequencing (COI + 16S + ND1 + 18S + 28S) and morphological analyses were conducted to delineate and identify species, and reconstruct phylogenetic relationships and population genetics. Specimens belonged to six native genera and nine species, of which seven are endemic to Borneo and three are new to science, i.e. Ctenodesma mawonae Zieritz et al., sp. nov., Sarawak basin, and Ctenodesma bersinara Zieritz et al., sp. nov., and Rectidens lauris Zieritz et al., sp. nov., both Pawan basin. Te monotypic genera Caudiculatus and Discomya were phylogenetically highly divergent from other known Gonideinae taxa, potentially indicating a separate tribe (for Caudiculatus) and subfamily (for Discomya). In addition, we report new records of the non-native Sinanodonta pacifca Heude, 1878 in the Batang Sadong and Kapuas river basins.